Closed Management System: Factors and Its Relationship to Students’ Academic Performance: Basis for Classroom Management Program - Liu, Jingkun; Dellova, Rovena I. (RSF Conference Series: Business, Management and Social Sciences, 2023)
Education has been a crucial aspect of social and economic development. As a result, countries invest immensely in their education systems for the students that will foster and learn different things. The study aims to explore the factors of a closed management system and how they affect students’ academic performance towards effective classroom management at Qingdao Vocational College of Aviation Technology in China. Using a descriptive research design with a quantitative approach using PLS-SEM, the researcher surveyed 341 respondents using the purposive sampling technique. The findings indicate that well-being significantly affects academic performance. The moderating effect of demographic profiles on factors and academic performance is observed. Notably, there is a research gap regarding the influence of the closed management system on students’ academic performance, particularly in China. Existing studies mainly focus on political and cultural variables influencing the educational system rather than specific mechanisms like the closed management system. This study fills the gap by providing a systematic and empirical analysis of the impact of the closed management system on the student’s academic performance. Today, there are limited studies on the impact of the closed management system on students ‘academic performance, especially in China. Existing studies concentrate on the political and cultural variables that influence the educational system rather than focusing on a particular mechanism. Thus, this aspect requires a systematic plan to manage the closed management system’s impact on the student’s academic performance.